2015
DOI: 10.1530/eje-15-0353
|View full text |Cite
|
Sign up to set email alerts
|

cAMP signaling in cortisol-producing adrenal adenoma

Abstract: The cAMP signaling pathway is one of the major players in the regulation of growth and hormonal secretion in adrenocortical cells. Although its role in the pathogenesis of adrenocortical hyperplasia associated with Cushing's syndrome has been clarified, a clear involvement of the cAMP signaling pathway and of one of its major downstream effectors, the protein kinase A (PKA), in sporadic adrenocortical adenomas remained elusive until recently. During the last year, a report by our group and three additional ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 58 publications
(78 reference statements)
0
26
0
1
Order By: Relevance
“…The p.L206R mutation is located in a highly conserved core of the domain responsible for the interaction between the regulatory and catalytic subunits of PKA (7). Functional experiments revealed that the mutation caused constitutive PKA activation, providing a molecular explanation for the development of CPA (7, 8). The mutation analysis suggests that the CYP11B2 positive tumor was the main source of autonomous aldosterone production and the CYP11B2 negative and CYP17 positive tumor was the main source of autonomous cortisol production in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p.L206R mutation is located in a highly conserved core of the domain responsible for the interaction between the regulatory and catalytic subunits of PKA (7). Functional experiments revealed that the mutation caused constitutive PKA activation, providing a molecular explanation for the development of CPA (7, 8). The mutation analysis suggests that the CYP11B2 positive tumor was the main source of autonomous aldosterone production and the CYP11B2 negative and CYP17 positive tumor was the main source of autonomous cortisol production in this case.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, recurrent activating mutations in PRKACA , encoding the catalytic subunit α of protein kinase A (PKA) have been identified in CPA (7). PRKACA gene mutations are found in 35-65% of the patients with CS (8). Herein, we report a case of PA and CS due to the co-existence of two adenomas harboring novel KCNJ5 somatic mutations and a PRKACA somatic mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the typical clinical picture, overt CS is associated with severe comorbidities and increased mortality (22,23). Patients whose tumors harbor PRKACA mutations present at a younger age at diagnosis, higher cortisol levels, and, interestingly, smaller-size tumors than CPAs without mutations (24,25).…”
Section: (± 02)mentioning
confidence: 99%
“…The protein hydrolyzes both cAMP and cGMP, regulating the intracellular concentration of cyclic nucleotides in the striatum [42]. As a target for signal transduction regulation, it has not been reported to have anticancereffects; however, cAMP mediates the translation of cancer cells into healthy cells [43, 44]. …”
Section: Resultsmentioning
confidence: 99%